ANALISIS PENGARUH KUALITAS PELAYANAN, KERAGAMAN PRODUK DAN IKLAN TERHADAP KEPUASAN KONSUMEN - Farikh Masruri, Abdul Halik, Donny Arif (IQTISHADequity jurnal MANAJEMEN, 2018)
The purpose of this research was to know and analyze the influence of the quality of services, the diversity of the products and advertising on consumer satisfaction. The technique of sampling method using accidental sampling that is made using anyone who is found by chance as a sample. Engineering data collection using the questionnaire by providing a list of the statement to the respondent. This study uses multiple linear regression tool. Based on the results of the analysis of the data obtained that ads and diversity in prouk partial effect positive and significant against the satisfaction of consumers, while the quality of service has no effect on customer satisfaction.  Keywords: service quality, product diversity, advertising, consumer satisfaction